Association between Chlamydophila pneumoniae and Atherosclerotic Plaques in Patients with Coronary Artery Disease and Abnormal Angiography - Frahad Abbasi; Darioush Iranpour; Kamran Mirzaei; Nahid Mohammadzadeh; Akram Najafi (Current Overview on Disease and Health Research Vol. 6, 2022)
One of the most crucial topics in the field of coronary artery diseases is the function of Chlamydophila pneumoniae in the pathogenesis of atherosclerosis. This study looked at the connection between atherosclerotic plaque and C. pneumoniae. Generally, C. pneumonia is one of important causes of pneumonia in human. In our study, Seropositivity of C. pneumoniae was checked in two groups: one group with significant coronary stenosis and one group with normal coronary angiography. In case and control groups, serum C. pneumoniae IgM and IgG antibodies was evaluated. Although the incidences of positivity were higher in the case group, there was no statistically significant difference in the seropositivity rates of IgM and IgG antibodies between the case and control groups. Our study’s findings did not identify a connection between acute or chronic C. pneumonia infection and atherosclerotic plaque or coronary artery stenosis. More precise studies are necessary to evaluate the probable inflammatory cascade that starts with C. pneumonia infection that may lead to development of atherosclerotic plaque.